A rare case of gastric perforation caused by Candida infection - Thakor, Mrugen; Chawla, Subhash; Utaal, Maneshwar Singh; De, Rijuta; Ramnani, Sakshi; Adlakha, Dakshita (International Surgery Journal, 2024)
Fungi are usually a rare cause of gastric perforation (about 0.65%), with most cases of gastric perforation occurring as complications of peptic ulcer disease (PUD), nonsteroidal anti-inflammatory drugs (NSAIDs) and gastric neoplasms. Here, we report the case of a 60-year-old male who presented to our hospital with severe epigastric pain, multiple episodes of vomiting and no history of PUD, NSAIDs use or gastric neoplasm. Exploratory laparotomy revealed a pre-pyloric gastric perforation which was repaired with modified graham’s patch repair. Histopathological examination of the gastric perforation edge biopsy revealed an intense Candida colonization invading and destroying the gastric wall. Intra-operative fluid sends for culture and sensitivity also revealed growth of candida species. He was subsequently treated with fluconazole antifungal and discharged home after an uneventful postoperative period.